Characterisation, Pathogenicity, And Mycotoxin Analysis Of Fungal Endophytes Of Corn (Zea Mays L.) In Peninsular Malaysia - Paul, Terna Tersoo (2022)
Endophytes are microbes that infect internal tissues of host plants for all or part of their life cycles, without causing any visible symptoms of disease. Depending on a number of factors such as the developmental stage of both host plant and fungus, environmental factors, and host defence responses, fungal endophytes indwelling tissues of host plants may become latent plant pathogens. In Peninsular Malaysia, works on endophytic fungi carried out so far have focused mainly on their ecological and functional roles in enhancing plant growth and other survival attributes, while much remains unknown regarding the disease initiation, and mycotoxin-producing potentials of fungal endophytes especially of corn and other cereal crops. Thus, the present study was carried out to identify, evaluate the pathogenicity, and investigate the mycotoxin-producing potentials of endophytic fungi resident in corn plants grown on different fields in Peninsular Malaysia. Using a combination of morphological and molecular techniques, endophytic fungi recovered from tissues of corn plants were identified in seven genera, namely Fusarium, Penicillium, Aspergillus, Aureobasidium, Cladosporium, Epicoccum, and Curvularia. Based on BLAST search and phylogenetic analysis of combined β-tubulin and TEF-1α sequences, endophytic Fusarium species isolated from corn plants were molecularly identified as F. pseudocircinatum, F. verticillioides, F. andiyazi, F. sacchari, F. mangiferae, F. fujikuroi, F. proliferatum, and F. incarnatum. Endophytic Penicillium species were identified as P. oxalicum, P. polonicum, and P. citrinum, based on ITS region and β- tubulin gene. Combined sequences of ITS region, β-tubulin, and Calmodulin genes were used to identify endophytic Aspergillus species as A. flavus, and A. tubingensis, ITS region and β-tubulin gene for the identification of A. pullulans, ITS region and ACT gene for identification of C. tenuissimum, while combined ITS region and LSU gene were used for identification of E. sorghinum and C. lunata.